O que mostram as demonstraç\~oes? Balanços e resultados dos bancos centrais - Antonio Carlos Macedo e Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– This paper deals with the financial statements of Central Banks. The starting point is the analysis of their balance sheets, which reveal their strong connections, on the one hand, with the National Treasuries; on the other hand, with the financial firms. The balance sheets reveal, besides the monetary policy instruments employed by the Central Bank, its structural liquidity position. If the banking system features a structural liquidity deficit, the Central Bank will provide the required reserves, so as to enforce its policy rate. In the opposite case - as in Brazil and many other developing countries - the Central Bank will be in the job of absorbing surplus liquidity. From the stocks, the paper moves on to flows, analyzing Central Banks' financial results, showing that they crucially depend on the institutions (including the accounting standards).
Keywords: E52; E58; 330; Central Bank; Monetary Policy